The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/advs.202300414
|View full text |Cite
|
Sign up to set email alerts
|

Autophagosomes Defeat Ferroptosis by Decreasing Generation and Increasing Discharge of Free Fe2+ in Skin Repair Cells to Accelerate Diabetic Wound Healing

Abstract: Ferroptosis plays an essential role in the development of diabetes and its complications, suggesting potential therapeutic strategies targeting ferroptosis. Secretory autophagosomes (SAPs) carrying cytoplasmic cargoes have been recognized as novel nano‐warrior to defeat diseases. Here, it is hypothesized that SAPs derived from human umbilical vein endothelial cells (HUVECs) can restore the function of skin repair cells by inhibiting ferroptosis to promote diabetic wound healing. High glucose (HG)‐caused ferrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Studies have shown that SAPs can promote the proliferation, migration, and tube formation of HG-HUVECs by reducing Fe 2+ accumulation and ROS production. 166 Another way to inhibit iron death is to use iron chelators such as deferoxamine (DFO) on the wound. Shao and colleagues prepared a gelatin microsphere containing DFO (DFO@G) through a reaction between the boronic acid group of 3-carboxy-4-fluorophenylboronic acid grafted quaternized CS and the hydroxyl group of PVA.…”
Section: Tissue Regenerationmentioning
confidence: 99%
“…Studies have shown that SAPs can promote the proliferation, migration, and tube formation of HG-HUVECs by reducing Fe 2+ accumulation and ROS production. 166 Another way to inhibit iron death is to use iron chelators such as deferoxamine (DFO) on the wound. Shao and colleagues prepared a gelatin microsphere containing DFO (DFO@G) through a reaction between the boronic acid group of 3-carboxy-4-fluorophenylboronic acid grafted quaternized CS and the hydroxyl group of PVA.…”
Section: Tissue Regenerationmentioning
confidence: 99%
“…More and more studies have shown that HG induces ferroptosis of endothelial cells participates in diabetes retinopathy, 89 diabetes atherosclerosis, 97 diabetic wounds, 98 and diabetes-related limb ischemia. 99 Previous studies have shown that glomerular endothelial cells ferroptosis plays an important role in the pathophysiological process of DN.…”
Section: Ferroptosis and Dnmentioning
confidence: 99%
“…In the context of DFU, ferroptosis expression is elevated [153], and has been demonstrated to mitigate ferroptosis and enhance healing [154]. The TP53 gene, a central player in DW, exhibits increased expression in diabetic foot tissue compared to healthy tissue [155].…”
Section: P53-dependent Panoptosis In Dwmentioning
confidence: 99%